Composição mineral, produção e qualidade de frutos de tangerina ‘Ponkan’ em função da correção do solo e adubação orgânica e mineral - Dias, Jefferson Alves (2015)
The low technology level employed by tangerine farmers in Paraíba State (Brazil) and the lack of knowledge of the nutritional management of the crop to improve the production quality lead to low productivity in that state. The use of well-established techniques like correction of the soil acidity through the application of limestone, addition of soil conditioner, and foliar biofertilizers reduce the costs with mineral fertilizers and improve production-quality attributes. Thus, the objective of this study was to evaluate the mineral composition in nitrogen, phosphorus, and potassium of the leaves; productivity; and fruit quality of the „Ponkan‟ citrus according to soil correction and organic and mineral fertilization. The experiment was carried out under field conditions from February to September of 2011 and 2012. The treatments were arranged in a randomized-block design with three replicates and eight plants per plot, using two useful plants, two plants as border on each of the sides, and one plant between the planting row, in a split-plot in time arrangement, in which the main plots were the eight treatments, and the sub-plots were the two years of evaluation. The treatments were: T1: no limestone; T2: application of limestone, according to the manual of fertilization recommendations of São Paulo State; T3: Limestone + Soil conditioner (every 30 days); T4: Soil conditioner (every 30 days); T5: Limestone + Foliar biofertilizer (every 30 days); T6: Foliar biofertilizer (every 30 days); T7: Foliar biofertilizer (at every 30 days) + Soil conditioner (every 30 days); T8: Limestone + Soil conditioner (every 30 days) + Foliar biofertilizer (every 30 days). The data were subjected to analysis of variance, and the effects of the treatments were broken down into non-orthogonal contrasts; the probabilities of the contrasts estimates were adjusted by the Bonferroni method. The applied treatments did not fully meet the „Ponkan‟ citrus‟s N and P requirements. Over the years, the treatments had a positive influence on the number of boxes (2.8 units), and productivity (56.6 t/ha) of the „Ponkan‟ citrus. The addition of soil conditioner after its correction with limestone and chemical fertilization increased the „Ponkan‟ citrus productivity by 202.9%. Soil correction and application of conditioner increased the soluble solids content of the „Ponkan‟ citrus. The correction of soil acidity combined with the application of soil conditioner and foliar biofertilizer increased the transverse diameter of the „Ponkan‟ citrus. The use of soil conditioner coupled with foliar biofertilizer reduced the „Ponkan‟ citrus firmness.